Principles and Best Practices in Successful Tourism Business Incubators - Andreea F. Schiopu; Dragoş C. Vasile; Claudia E. Ţuclea (Amfiteatru Economic Journal, 2015)
The business incubators are entities that provide support to start-up companies, managing the obstacles faced by entrepreneurs and facilitating the hazardous process of business creation. This article aims to identify the existing views on best practices that can contribute to the achieving of business incubators' objectives. Moreover, the present study investigates how the business incubators can ensure the success of tourism, with evidence grounded in both theory and case studies from around the world. In this paper, the authors have identified several types of incubators that could be used successfully for the benefit of start-ups in the tourism sector, such as network incubators, incubators in ecotourism or nature-based incubators. The authors also propose a new perspective on best practices in business incubation, emphasizing the role of the emotions that entrepreneurs have to cope with. Even though the studies in this area are still scarce, the authors strongly believe that this will be a topic highly discussed in the near future, given the fact that emotion and logical thought are intertwined, interacting in complex ways during problem solving, decision making, and other important forms of cognition that entrepreneurs use when pursuing their ventures.
Keywords: M10; M13; Q01; Q26; 330; best practices; business incubators; tourism business incubators; emotions; entrepreneurship